The Efforts to Improve the Attitude of Love Culture through Karawitan Extracurricular Activities in Elementary School - Endang Sri Maruti; Muti Atul Maskurin; Nanda Saputra (Britain International for Academic Research (BIAR-Publisher), 2021)
This study aims to improve the attitude of love culture with Karawitan extracurricular activities to student’s of SDN 01 Manisrejo, Madiun City. This study is a Classroom Action Research (CAR). The subjects of this study were all students who followed Karawitan's extracurricular strength which amounted to 24 students. Data collection techniques used were observation, questionnaires, and tests. The data analysis technique was carried out in a qualitative descriptive manner. The results show that Karawitan extracurricular activities can enhance students' cultural love attitude. In the first cycle there were only 19 students or 79.2% who could achieve indicators of cultural love attitude. Whereas in the second cycle there was an increase in the number of students who could reach 24 indicators of cultural love attitudes or 100%. In addition, student activity and learning outcomes also increased. In the first cycle, 75% of the number of students had begun to be active and in the second cycle had increased to 87.5% of the number of students already active during the learning process. While for the percentage of learning outcomes in the first cycle there are 75% of the number of students who have reached the indicator and in the second cycle 91.7% of the total students have achieved the expected learning outcomes indicators.